2021
DOI: 10.3389/fnut.2021.623336
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Online Learning to Promote Systems Thinking for Sustainable Food Systems Training in Dietetics Education

Abstract: Educating and training a multisectoral food systems workforce is a critical part of developing sustainable, resilient, and healthy food and water systems. This paper shares perspectives from a working group of educators, learners, and food systems subject matter experts that collaborated over the course of a year to develop, pilot test, and evaluate two interactive webinar series with a multi-site cohort of dietetics interns and graduate students. The three-part webinar series format included a training webina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…9,27 Most of the articles were from North America, including the United States (n = 4; 33%) and Canada (n = 4; 33%), 17,34,[36][37][38][39][40][41] with the remainder from Australia (n = 2; 17%), 35,42 New Zealand (n = 1, 8%) and Spain (n = 1, 8%) (Table 4). 43,44 The study designs included six case studies report, [34][35][36][37][38][39] four intervention studies, 17,[42][43][44] an exploratory study 40 and a descriptive study. 41 No consistency was apparent when considering the number or the timing of learning activities, in the dietetics program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,27 Most of the articles were from North America, including the United States (n = 4; 33%) and Canada (n = 4; 33%), 17,34,[36][37][38][39][40][41] with the remainder from Australia (n = 2; 17%), 35,42 New Zealand (n = 1, 8%) and Spain (n = 1, 8%) (Table 4). 43,44 The study designs included six case studies report, [34][35][36][37][38][39] four intervention studies, 17,[42][43][44] an exploratory study 40 and a descriptive study. 41 No consistency was apparent when considering the number or the timing of learning activities, in the dietetics program.…”
Section: Resultsmentioning
confidence: 99%
“…37,44 There was variability in the teaching approaches used to enhance student knowledge of sustainability. Three articles reported that the learning activity focused on content knowledge, [35][36][37] problem-based learning techniques were used in four articles, 17,34,43,44 and experiential learning activities were embedded in the curricula in five articles. [38][39][40][41][42] Of the three articles that focused on content knowledge, the learning outcomes based on the Kirkpatrick-Barr framework varied.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of empirical research, in addition to surveys, interviews and focus group discussions, no one method stands out. However, researchers, including Iordache-Platis (2020) and Spiker et al, (2021), have begun building a theoretical foundation and developing frameworks which are equally beneficial for the stakeholders in academic research. Normally, empirical research consists mainly of quantitative, qualitative, and triangulation as methods.…”
Section: Article Classification Based On Research Methods and Designmentioning
confidence: 99%
“…Other domains included soil protection (Lobry et al, 2017),clinical care (King, et al, 2021) ,plant genetics (Achigan-Dako et al, 2014),energy issues (Popescu & Avram, 2020),animal feeding (Islam et al, 2021),foodstuff (Spiker et al, 2021),agroecology (Wezel et al, 2018),law (Wahid et al, 2018),health (Brandão et al, 2022),climate issues (Noy et al,, 2021) Teaching in Higher Education 64…”
Section: Article Classification Based On Publication Yearmentioning
confidence: 99%
See 1 more Smart Citation